Analisis Peningkatan Literasi Statistik Mahasiswa pada Mata Kuliah Statistika Pendidikan berbasis The Statistical Process - Zulqoidi R. Habibie; Puput Wahyu Hidayat (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
One of the competencies that students must have in the 21st century is statistical literacy skills. To fulfill this, the researcher conducted research on 33 students of education statistics for 16 meetings to analyze the increase in statistical literacy of elementary school teacher candidates. Mixed-Methods with Competitor Embeded design will be used in this study, which is a qualitative research complementing quantitative research. Research data were obtained from test instruments (pre-test and post-test) which were developed based on statistical processes and non-test instruments (results from interviews). For more in-depth analysis, the data is seen based on the Initial Statistics ability, namely: high, medium, and low. The results of this study indicate that the statistical literacy of prospective elementary school teacher students increases both in the high group, medium group, and low group after participating in statistical learning for 16 meetings, serving students outside class hours is one of the factors in increasing student learning motivation which has a direct impact on student learning progress, and teaching methods. This research still has shortcomings that can be used as a reference for further research, one of which is the absence of a consistent method used in teaching one semester. For this reason, further research needs to use learning methods in increasing student statistical literacy.